High condylectomy procedure: A valuable resource for surgical management of the mandibular condylar hyperplasia - Pereira-Santos, Darklilson; De Melo, Willian Morais [UNESP]; Souza, Francisley Ávila [UNESP]; De Moura, Walter Leal; De Paulo Cravinhos, Julio César (Wolters Kluwer, 2013)
Condylar hyperplasia is an overdevelopment of the condyle, which may manifest unilaterally or bilaterally. This pathological condition can lead to facial asymmetry, malocclusion, and dysfunction of the temporomandibular joint. The etiology and pathogenesis of condylar hyperplasia remain uncertain, but it has been suggested that its etiology may be associated with hormonal factors, trauma, and hereditary hypervascularity, affecting both genders. The diagnosis is made by clinical examination, and radiological imaging, and additionally, bone scintigraphy, is a fundamental resource for determining whether the affected condyle shows active growth. Patients with active condylar hyperplasia management have better results when they are subjected to the high condylectomy procedure. The authors report a case in a 20-year-old female subject with unilateral active condylar hyperplasia who was treated by high condylectomy. The patient has been followed up for 4 years without signs of recurrence and with good functional stability of the occlusion. © 2013 by Mutaz B. Habal, MD.
Keywords: Condylar hyperplasia; facial asymmetry; recurrence; surgical management